Security System With QR CODE Model For Digital Certificated Using Hash Function MD5 - fandi, Fandi ahmad; Furqan, Mhd; Armansyah (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2025)
A digital certificate is an official declaration of recognition that is usually given to particular people or organizations in appreciation of their education, experience, and skill. Because of their ability to reduce paper usage and improve operational efficiency, these certificates have become increasingly popular in today's digital environment, being used for a variety of purposes and replacing traditional paper certificates. But since digital certificates are stored in a digital file format, malicious actors can easily manipulate them. Known for being a one-way encryption method, the MD5 hash function converts messages of any length into a fixed-length string of 128 bits. The MD5 hash function is primarily used to confirm the legitimacy of files. It makes it easier to compare the calculated hash value with the original, protecting the integrity of the data. Meanwhile, two-dimensional matricies represented graphically as QR Codes are flexible data storage devices that can hold binary, alphanumeric, and numeric data. By combining the MD5 hash function with QR Regulations, data can be given a distinct identity that enhances its authenticity and prevents attempts at forgery or replication. This combination strengthens data security protocols, which is a vital requirement in a time when digital data powers many aspects of modern life.